Probabilistic Models. - Onsi, Mohamed; Bruns, William J. (The Accounting Review, 1968)
Reviews the book "Probabilistic Models," by Clifford H. Springer, Robert E. Herlihy, Robert T. Mall and Robert I. Beggs.